Strategic planning: perceptions about the importance of this management tool - Lorenzett, Daniel Benitti; Wegner, Roger da Silva; Godoy, Leoni Pentiado; Rodrigues, Marlene Kreutz (Revista de Administração da UFSM, 2020)
Purpose – Strategic planning is a management tool that allows you to establish the strategies that an organization will adopt to achieve its vision of the future and fulfill its proposed mission. In this way, it defines the objectives, means and resources needed to achieve them. Thus, this study aimed to analyze the elements of strategic planning in a group of micro and small service companies located in the central region of Rio Grande do Sul. Design/methodology/approach – To perform the research was carried out a field research, which had data collection. This was done by applying a questionnaire to a group of 25 companies in the service segment, assisted by an extension project. Findings – Results showed that the vast majority of these companies use some elements of strategic planning in their management practice, such as: insurance contracting, the use of outsourced labor, the existence of established operating procedures, the presence and exposure of general organization chart, employees' knowledge of the general organization chart, the presence of documented standards, the existence of a flowchart and its disclosure to employees, even if in an unstructured manner. This finding demonstrates the need for greater specialization of micro and small entrepreneurs to manage their organizations. Originality/value – This study opens the way to highlight the importance of studying the highlighted theme, favoring decision making, in addition to contributing to the literature, deepening the debate on strategic planning in micro and small companies.